Increased Ghrelin but Low Ghrelin-Reactive Immunoglobulins in a Rat Model of Methotrexate Chemotherapy-Induced Anorexia - François, Marie; Takagi, Kuniko; Legrand, Romain; Lucas, Nicolas; Beutheu, Stephanie; Bôle-Feysot, Christine; Cravezic, Aurore; Tennoune, Naouel; do Rego, Jean-Claude; Coëffier, Moïse; Inui, Akio; Déchelotte, Pierre; et al. (Frontiers in Nutrition, 2016)
Background and aims: Cancer chemotherapy is commonly accompanied by mucositis, anorexia, weight loss and anxiety independently from cancer-induced anorexia-cachexia, further aggravating clinical outcome. Ghrelin is a peptide hormone produced in gastric mucosa that reaches the brain to stimulate appetite. In plasma, ghrelin is protected from degradation by ghrelin-reactive immunoglobulins (Ig). To analyze possible involvement of ghrelin in the chemotherapy-induced anorexia and anxiety, gastric ghrelin expression, plasma levels of ghrelin and ghrelin-reactive IgG were studied in rats treated with methotrexate (MTX). Methods: Rats received MTX (2.5 mg/kg, S.C.) for three consecutive days and were killed 3 days later, at the peak of anorexia and weight loss. Control rats received phosphate-buffered saline. Preproghrelin mRNA expression in the stomach was analyzed by in situ hybridization. Plasma levels of ghrelin and ghrelin-reactive IgG were measured by immunoenzymatic assays and IgG affinity kinetics by surface plasmon resonance. Anxiety- and depression-like behaviors in MTX-treated anorectic and in control rats were evaluated in the elevated plus-maze and the forced-swim test, respectively. Results: In MTX-treated anorectic rats the number of preproghrelin mRNA-producing cells was found increased (by 51.3%, p<0.001) as well were plasma concentrations of both ghrelin and des-acyl-ghrelin (by 70.4%, p<0.05 and 98.3%, p<0.01, respectively). In contrast, plasma levels of total IgG reactive with ghrelin and des-acyl-ghrelin were drastically decreased (by 87.2% and 88.4%, respectively, both p<0.001), and affinity kinetics of these IgG were characterized by increased small and big Kd, respectively. MTX-treated rats displayed increased anxiety- but not depression-like behavior. Conclusion: MTX-induced anorexia, weight loss and anxiety are accompanied by increased ghrelin production and by a decrease of ghrelin-reactive IgG levels and affinity binding properties. Such changes of ghrelin-reactive IgG may underlie their decreased ghrelin transporting capacities compromising ghrelin orexigenic and anxiolytic effects and contributing to chemotherapy-induced loss of appetite.